Possibilities of modern procedures in gingival recession therapy - Janković Saša; Dimitrijević Božidar (Serbian Medical Society - Dental Section, Belgrade, 2003)
This study was designed to compare the effectiveness and predictability of GTR and connective tissue graft in the treatment of gingival recession. 15 recessions Miller class II and III were treated with bioabsorbable barrier and coronally advanced flap. The same number of defects was treated with connective tissue graft in combination with coronally advanced flap. Clinical recordings included hygiene standards and recession depth (RD) probing depth (PD), clinical attachment level (CAL) and keratinized tissue width (KT) Mean (RD) was statistically significant decreased from 5,47mm presurgery to 0.73mm with GTR (87,76%) and from 5,93mm to 0.60 with CTG (89.9%). Prevalence of complete root coverage was 40% for the GTR and 46,66% for CTG group. No statistically significant differences between treatment groups were observed in this study Treatment of gingival recessions with CTG and GTR present effective and highly predictable mucogingival plastic surgical procedures.